η-Intuitionistic Fuzzy Soft Groups - Kurfia, Mustika Ana; Hidayat, Noor; Karim, Corina (Mathematics Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
In this research, we present the idea of the intuitionistic fuzzy soft group defined on the intuitionistic fuzzy soft set. The main purpose of this research is to create a new concept, which is an intuitionistic fuzzy group. To achieve this, we combine the concept of intuitionistic fuzzy group and intuitionistic fuzzy soft group. As the main result, we prove the correlation between the intuitionistic fuzzy soft group and intuitionistic fuzzy soft group along with some properties of intuitionistic fuzzy soft groups. Also, we prove some properties of a subgroup of an intuitionistic fuzzy soft group. An intuitionistic fuzzy soft homomorphism is also proved.